CHARACTERIZATION OF MECHANICAL PROPERTIES: TITANIUM VS. STEEL IN THE BATTLE OF ORTHODONTIC MINI-IMPLANTS - Tinela Panaite; Cristian Liviu Romanec; Carmen Savin; Mihnea Iacob; Raluca Maria Vieriu; Alice Chehab; Irina Nicoleta Zetu; Carina Balcos (Romanian Journal of Oral Rehabilitation)
The mechanical properties of orthodontic mini-implants play a critical role in their performance, stability, and durability during treatment. This study investigates the tensile behavior of mini-implants fabricated from titanium alloy (Ti6Al4V) and stainless steel (316L) through tensile testing. The experiments were conducted using the INSTRON 34SC-5 servohydraulic system under controlled conditions to evaluate parameters such as ultimate tensile strength (σUTS), yield strength (σy), elongation at fracture, and modulus of elasticity.The results demonstrate that titanium mini-implants exhibit higher deformation energy storage and superior ductility compared to stainless steel, with σUTS values of 488 MPa and 462.6 MPa, respectively. However, both materials displayed predominantly brittle fracture behavior. Significant differences in elongation at fracture highlight the titanium alloy's enhanced capacity to absorb energy through plastic deformation, ensuring greater reliability under mechanical forces.This study emphasizes the importance of tensile strength and ductility in material selection for mini-implants, as they directly influence stability, resistance to mechanical stresses, and clinical performance. Insights gained from tensile testing contribute to optimizing the design and manufacturing of mini-implants, ensuring their integrity under orthodontic loads and improving treatment outcomes. The findings underscore the potential of titanium alloys in providing superior mechanical properties, making them the preferred choice for advanced orthodontic applications.